Free virtual science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The electronic version of the science journal Nature is one of the latest being made freely available online to countries with a GNP below US$ 1,000 per capita. Free access to about 2,000 scientific journals, from Blackwell, Elsevier and John Wiley...